Integrating Technology Adoption, Knowledge Sharing, and Financial Planning to Enhance Business Performance: A Model for F&B MSMEs in Jakarta - Syahyono, Syahyono; S. Syahyono (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This study explores the impact of technology adoption, knowledge sharing, and financial planning on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage (F&B) sector in Jakarta, Indonesia. The research aims to develop an integrated model that illustrates how these factors contribute to improving business performance, particularly in the context of emerging markets. Using a quantitative approach, data was collected from 770 respondents via a survey, and Structural Equation Modeling (SEM) was employed to analyze the relationships between variables. The findings indicate that technology adoption significantly influences strategic absorptive capacity, which in turn enhances financial planning and business performance. Knowledge sharing was found to positively affect financial planning, but its direct impact on strategic absorptive capacity was weak. The study concludes that strengthening absorptive capacity and financial planning are critical for MSMEs to achieve sustainable growth and competitiveness in the digital age. This research offers valuable insights for MSME owners and policymakers aiming to improve the business performance of MSMEs through technology and knowledge integration.